2017
DOI: 10.1186/s13011-017-0131-4
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to receive intravenous buprenorphine treatment in opioid-dependent people refractory to oral opioid maintenance treatment: results from a community-based survey in France

Abstract: BackgroundInjectable opioids are an interesting option for people who inject drugs (PWID) that do not respond to oral Opioid Maintenance Treatment (OMT). To date, intravenous (IV) buprenorphine - a safer drug than full-opioid agonists in terms of overdose risk - has never been tested in a clinical trial on opioid dependence. We designed a survey to better understand the profile of PWID eligible for IV buprenorphine, and their willingness to receive it.MethodsThis cross-sectional community-based national survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…This is the reason why public health researchers, clinical experts and the PWID community, came together in 2015 to set up a project to evaluate the feasibility and efficacy of IV buprenorphine as a prescribed treatment in France. The first step of this project was to implement a community-based research study, entitled PrebupIV, to characterize people who inject opioids, and to evaluate their willingness to receive this potential treatment [ 22 ]. The community-based aspect of PrebupIV focused on involving people who inject opioids in the development of IV buprenorphine as a treatment, through their participation in the research process and dissemination of the results.…”
Section: Introductionmentioning
confidence: 99%
“…This is the reason why public health researchers, clinical experts and the PWID community, came together in 2015 to set up a project to evaluate the feasibility and efficacy of IV buprenorphine as a prescribed treatment in France. The first step of this project was to implement a community-based research study, entitled PrebupIV, to characterize people who inject opioids, and to evaluate their willingness to receive this potential treatment [ 22 ]. The community-based aspect of PrebupIV focused on involving people who inject opioids in the development of IV buprenorphine as a treatment, through their participation in the research process and dissemination of the results.…”
Section: Introductionmentioning
confidence: 99%
“…The choice to take morphine sulfate instead of other OST may be related to its stronger "high" effect and this may be the reason for the greater loss of libido reported in this population. The PrebupIV survey (Roux et al, 2017) showed that morphine sulfate was used to get high more frequently than methadone and buprenorphine. Another French survey investigating this substance reported that 77.6% of users were searching for a rewarding effect (Peyriere et al, 2016).…”
Section: 0discussionmentioning
confidence: 99%
“…PrebupIV is a cross-sectional community-based participatory research study performed by the association AIDES and the French national institute for medical research (INSERM) in collaboration with other associations (Fédération Addiction, ASUD, Médecins du Monde). Its aim was to assess acceptability of a novel intravenous buprenorphine treatment (Roux et al, 2017). It was conducted in France between May and August 2015 in low-threshold addiction centers (free centers which provide various services, including needle exchange programs, where no requirements are needed for attendance), in general practitioner offices, in community-based associations, and through the French drug-use self-help website Psychoactif.org.…”
Section: 1study Designmentioning
confidence: 99%
See 2 more Smart Citations